Thor's Microsoft security bible : a collection of practical security techniques - Mullen, Timothy M. (Syngress, 2011)
Thor's Microsoft Security Bible provides a "one-stop-shop" for Microsoft-related security techniques and procedures as applied to the typical deployment of a Microsoft-based infrastructure. The book contains detailed security concepts and methodologies described at every level: Server, Client, Organizational Structure, Platform-specific security options, application specific security (IIS, SQL, Active Directory, etc.) and also includes new, never-before-published security tools complete with source code. Detailed technical information on security processes for all major Microsoft applications Unique project-based "storytelling" delivery, combining multiple security techniques and methods together for real-world solutions to security challenges in actual business use cases Reference-style content for access to specific application security techniques and methods Actual author opinion and guidance as not only HOW to go about security particular applications, but WHY to do so DVD Companion disk with source code, tools, video tutorials, and other materials